Étude et mise en place d'un progiciel décisionnel pour l'optimisation et la synchronisation du flux de la chaine logistique du site marly la ville (2006)
The logstic process that takes place in the branch of DAHER located in the city of Mary-la- Ville, concerns just one client in the telephony industry. This branch. inaugurated five years ago. has followed several evolutions with reference to the logistics chain in order to adapt it to the arriving changes like the amount of products to be packed, the type of package used, the restrictions established by the destination country or the final client. This chain is composed by four important sections: reception of the products, preparation, packing and expedition of the customer orders. At present, this chain doesn't have a production control system allowing the different means ¿ human, material, financial ¿ to be adapted in real time and in the short-term in order to finally optimise the flow of the activities. Within this context, my mission consists in a first time, to conceive the production control system and then...